Hec1 and Nuf2 Are Core Components of the Kinetochore Outer Plate Essential for Organizing Microtubule Attachment Sites - DeLuca, Jennifer G. (The American Society for Cell Biology, 2005)
A major goal in the study of vertebrate mitosis is to identify proteins that create the kinetochore-microtubule attachment site. Attachment sites within the kinetochore outer plate generate microtubule dependent forces for chromosome movement and regulate spindle checkpoint protein assembly at the kinetochore. The Ndc80 complex, comprised of Ndc80 (Hec1), Nuf2, Spc24, and Spc25, is essential for metaphase chromosome alignment and anaphase chromosome segregation. It has also been suggested to have roles in kinetochore microtubule formation, production of kinetochore tension, and the spindle checkpoint. Here we show that Nuf2 and Hec1 localize throughout the outer plate, and not the corona, of the vertebrate kinetochore. They are part of a stable “core” region whose assembly dynamics are distinct from other outer domain spindle checkpoint and motor proteins. Furthermore, Nuf2 and Hec1 are required for formation and/or maintenance of the outer plate structure itself. Fluorescence light microscopy, live cell imaging, and electron microscopy provide quantitative data demonstrating that Nuf2 and Hec1 are essential for normal kinetochore microtubule attachment. Our results indicate that Nuf2 and Hec1 are required for organization of stable microtubule plus-end binding sites in the outer plate that are needed for the sustained poleward forces required for biorientation at kinetochores.